Intercropping system affect PH, moisture content and the presence of nitrogen, phosphorus and potassium (NPK) in soil at Karas plantation area - Husni Ibrahim (Tanjong Malim, 2019)
Intercropping system affect PH, moisture content and the presence of nitrogen, phosphorus and potassium (NPK) in soil at Karas plantation area by Husni Ibrahim